The Effect of Substituting Wheat Flour with Composite Flour (Cucurbita moschata and Daucus carota L.) on Biscuits as a Source of Beta Carotene for Stunted Children - Asysyifa Riana; Hari Hariadi; Yuliati Widiastuti; Iriyanti Harun; Galuh Chandra Irawan; Lanny Tantie; Kartika Anzani; Firman Rezaldi; Andri Tri Cahyono (Universitas Islam Negeri Ar-Raniry, 2024)
The problem of stunting in Indonesia is still quite high, namely 21,6% based on data from the 2022 Indonesian Nutrition Status Survey (SSGI). One of the effective measures to control stunting is through providing additional food (PMT) such as biscuits to children. Carrots and pumpkin are local foods that are rich in beta carotene. Carotenoids as a source of provitamin A are able to overcome the problem of vitamin A deficiency (VAD), which is the cause of growth disorders in children. This research aims to determine the effect of substitution of yellow pumpkin (Cucurbita moschata) and carrot (Daucus carota L.) composite flour on organoleptic characteristics including color, aroma, taste, texture and nutritional content (beta carotene, carbohydrates, protein and fat). This research used a Randomized Block Design (RAK) with 3 treatments, namely formula 1 (150 grams of wheat flour, 50 grams of pumpkin flour and 50 grams of carrot flour), formula 2 (50 grams of wheat flour, 60 grams of pumpkin flour and 50 grams of flour carrots) and formula 3 (50 grams of wheat flour, 50 grams of pumpkin flour and 150 grams of carrot flour) with 3 repetitions. The research results showed that formula 3 biscuits were the best formulation in terms of organoleptic characteristics with the highest beta carotene content compared to F1 and F2. F3 biscuits contain 30,97 mg beta carotene, 7,45 grams of carbohydrates, 3,22 grams of protein and 8,89 grams of fat. The conclusion of this research is that the substitution of wheat flour with composite flour (Cucurbita moschata and Daucus carota L.) has an effect on the nutritional content (beta carotene, carbohydrates, protein and fat) of biscuits. Consuming pumpkin biscuits per 100 grams can qualify as a good source of the antioxidant beta carotene.